2011
DOI: 10.1016/j.bbrc.2011.09.115
|View full text |Cite
|
Sign up to set email alerts
|

Green tea polyphenol epigallocatechin-3-gallate suppresses melanoma growth by inhibiting inflammasome and IL-1β secretion

Abstract: Epigallocatechin-3-gallate (EGCG), the major polyphenolic component of green tea, has been demonstrated to possess anti-inflammatory, antioxidant, anti-mutagenic and anti-carcinogenic properties. The anti-melanoma effect of EGCG has been previously suggested, but no clear mechanism of action has been established. In this study, we demonstrated that EGCG inhibits melanoma cell growth at physiological doses (0.1–1 μM). In the search for mechanisms of EGCG-mediated melanoma cell suppression, we found that NF-κB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(110 citation statements)
references
References 30 publications
2
102
1
1
Order By: Relevance
“…The anti-inflammatory activity of polyphenols in green tea extract (GTE) has been demonstrated in various models of acute inflammation (Singh et al 2010;Relja et al 2012;Shen et al 2011Shen et al , 2012, and numerous mechanisms have been suggested for their anticancer activities including suppression of NF-kappaB, inflammasome, and IL-1beta secretion (Lamoral-Theys et al 2010;Ellis et al 2011). Many malignancies are characterized by an activation of interleukin-associated kinases, and several drugs targeting specific kinases, both natural and synthetic, are being used for cancer treatment (Guo et al 2015;Kim et al 2015).…”
Section: Green Tea Has Anti-inflammatory and Anticancer Propertiesmentioning
confidence: 99%
“…The anti-inflammatory activity of polyphenols in green tea extract (GTE) has been demonstrated in various models of acute inflammation (Singh et al 2010;Relja et al 2012;Shen et al 2011Shen et al , 2012, and numerous mechanisms have been suggested for their anticancer activities including suppression of NF-kappaB, inflammasome, and IL-1beta secretion (Lamoral-Theys et al 2010;Ellis et al 2011). Many malignancies are characterized by an activation of interleukin-associated kinases, and several drugs targeting specific kinases, both natural and synthetic, are being used for cancer treatment (Guo et al 2015;Kim et al 2015).…”
Section: Green Tea Has Anti-inflammatory and Anticancer Propertiesmentioning
confidence: 99%
“…This compound also exhibited a considerable apoptotic effect against mouse hepatoma cell lines by cleaving procaspase-12 and increase in phosphorylation of ElF2 (subunit of ElF2 protein, responsible for an important regulator of translation initiation) [192]. Ellis et al [193] uncovered the underlying EGCG-induced melanoma inhibition mechanism by using EGCG against melanoma cancer cell lines. According to these authors, the downregulation of inflamasommes (multiprotein oligomer) decreases the secretion of IL-1 (a cytokine) which in turn decreases the activity of NF-kB that finally reduces cell growth.…”
Section: Flavanolsmentioning
confidence: 99%
“…Both indicate that despite the remarkable effect of this compound on in vitro and in vivo assays, clinical trials have failed to come up with standardized methods to test this compound, making it difficult to draw satisfactory conclusions and urging researchers to rethink and design common clinical trials for this natural compound [207,208]. The clinical trials against cancer using genistein studied both the joint activity of genistein with other drugs (gemcitabine and [193] (-) Epigallocatechin-3-gallate monoesters Colorectal carcinoma In vitro human cell lines Inhibition of cell proliferation Apoptosis induction Reduction in hydrogen peroxide production [194] Metachronous adenomas of the colorectum Epidemiological studies Ongoing [196] Breast carcinoma Epidemiological studies Ongoing [197] Epigallocatechin-3-gallate Lung carcinoma Epidemiological studies Ongoing [198] erlotinib) and the pharmacokinetics of this drug, along with the traditional trials against bladder, breast and pancreatic cancer [209][210][211][212][213]. Currently, on-going clinical trials are studying genistein against prostate, bladder, lung and kidney cancers, as well as melanoma [214][215][216][217][218].…”
Section: Isoflavonesmentioning
confidence: 99%
“…Epigallocatechin-3-gallate (EGCG), the most active compound in the catechin family of green tea extracts, has been shown to have both anti-inflammatory and antioxidant properties on multiple cell types in in vitro studies [12,13]. We therefore decided to use it as a comparative group against our CA and CGA groups.…”
Section: Introductionmentioning
confidence: 99%